Association between periodontitis and postoperative complications in hospital medical surgical procedures: a systematic review - Cueto Urbina, Alfredo (2023)
Background: Periodontitis is potentially harmful in the perioperative period due to biofilm generating a environment for bacteria to spread and colonize other anatomical areas, which can generate a potential risk of infection, delayed healing, increased morbidity, and even induce avulsion in intubated patients, and subsequent aspiration or ingestion of teeth with increased mobility. Objective: Associate the presence of periodontitis and postoperative complications in patients who underwent an in-hospital medical surgical procedure. Methods: A systematic review based on studies extracted from PubMed and Scopus was carried out on June 10, 2020, based on the Population, Intervention, Comparison and Result search strategy. As inclusion criteria, the studies had to include all the disaggregated terms of the research question, have a publication date of less than 15 years, and the target population had to have undergone elective hospital medical-surgical interventions. The exclusion criteria corresponded to not presenting an analytical or experimental observational study design, not having made a periodontal clinical diagnosis of the study subjects, and not expressing in the results the presence of postoperative medical-hospital complications. Articles were assessed for quality by supplementing the STROBE guideline and Newcastle Ottawa, for risk of bias by supplementing the STROBE guideline and the Cochrane Collaboration handbook tool. Results: A total of 131 articles were obtained, which were subjected to a selection process, resulting in 5 final analytical observational studies. A meta-analysis was performed and determined that periodontitis was a risk factor to postoperative complications after surgical procedures with an OR = 4,76; 95%CI [1,11-20,41]. Conclusions: Optimize the guidelines for assessing quality and risk of bias can make their comparison with other studies complex, however it was determined in a statistically significant way that patients with periodontitis have a higher risk of   generating postoperative complications after a medical hospital surgery.